PENGARUH EARNING PER SHARE, FIRM SIZE, DAN SALES GROWTH TERHADAP DIVIDEND PAYOUT RATIO (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (TAHUN 2014 SAMPAI TAHUN 2018 - Siti Nurlatifah, SE., M.Si. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The purpose of this study is to determine the effect of earnings per share, firm size, and sales growth on the dividend payout ratio. The population used is the food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018 as many as 26 and the sample in this study were 7 companies determined through purposive sampling. This study uses simple regression analysis techniques and multiple regression and uses SPSS 25 program analysis tools. The results of the t test (partial) show that earning per share variable has a negative and not significant effect on dividend payout ratio. Firm size variable has a positive and significant effect on dividend payout ratio. Sales growth variable has positive and significant effect on dividend payot ratio. The F (simultaneous) test results show that the earnings per share, firm size, and sales growth variables simultaneously have a significant effect on the dividend payout ratio.